2014
DOI: 10.7205/milmed-d-12-00545
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Bioelectrical Impedance Analysis and Skinfold Thickness in Predicting Body Fat in Military Personnel

Abstract: Previous studies show that body composition is related to injury risk and physical performance in soldiers. Thus, valid methods for measuring body composition in military personnel are needed. The frequently used body mass index method is not a valid measure of body composition in soldiers, but reliability and validity of alternative field methods are less investigated in military personnel. Thus, we carried out test and retest of skinfold (SKF), single frequency bioelectrical impedance analysis (SF-BIA), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 40 publications
1
74
0
2
Order By: Relevance
“…For example, De Lorenzo et al [16], reported BIA underestimated true %BF by 2.6 %BF; however, their criterion measure was DXA and not the BOD POD ® , and they evaluated whole-body BIA. Conversely, other studies using part or whole-body BIA have not observed signi icant differences with %BF measures taken from the DXA [9,13,22] or the BOD POD ® [23]. The type of BIA (i.e., lower body versus upper body) is an unlikely source of variance for comparing validity between studies because lower-body and upper-body BIA are highly correlated with each other [9] as well as with whole-body measures of impedance [22].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…For example, De Lorenzo et al [16], reported BIA underestimated true %BF by 2.6 %BF; however, their criterion measure was DXA and not the BOD POD ® , and they evaluated whole-body BIA. Conversely, other studies using part or whole-body BIA have not observed signi icant differences with %BF measures taken from the DXA [9,13,22] or the BOD POD ® [23]. The type of BIA (i.e., lower body versus upper body) is an unlikely source of variance for comparing validity between studies because lower-body and upper-body BIA are highly correlated with each other [9] as well as with whole-body measures of impedance [22].…”
Section: Discussionmentioning
confidence: 88%
“…Single frequency BIA has very high reliability [13]; however, research on the validity of BIA is equivocal with some reporting strong validity, [13,15] and others raising questions about its validity [6,16,17]. We have observed anecdotally that %BF estimates derived using hand-held BIA are in luenced systematically by elbow position (i.e., lexed versus fully extended).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, physical load was assessed using heart rate monitoring [10,11,17], energy intake based on self-reported food logs [16], and doubly-labelled water [14], the latter being considered as having great validity for use in field studies [29]. Body mass composition has been assessed using skinfold measurements [16,17] or bioelectric impedance analysis [12,13,17], the latter being considered as having greater validity compared with the former, although this might vary depending on the device and type of equation used [30]. For example, Weydahl and Calogiuri [17] used a hand-to-hand device, which is considered as having smaller validity as compared with the full-body assessments used by Case et al .…”
Section: Quality Of the Studiesmentioning
confidence: 99%
“…Gold-standard methods are available to assess BC (e.g., hydrostatic weighing), but are generally restricted to clinical settings [5]. BC assessment is more commonly conducted using one of several different field techniques, which individually are considered valid tests [6]. Anecdotal evidence has suggested, however, that some individuals may rank relatively high when assessed by one method and relatively low when assessed by another method.…”
Section: Introductionmentioning
confidence: 99%